ACTOR COLLABORATION MODEL EXTREME POVERTY ERADICATION IN LOCAL GOVERNMENT - Lisa Aryani; Novita Tresiana; Noverman Duadji (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
Extreme poverty remains a serious problem in various regions and requires an approach that involves many parties collaboratively, especially at the local government level that is directly in touch with the dynamics of community life. A number of previous studies, both at the global and national levels, have examined poverty alleviation strategies through various approaches such as economic empowerment, government cooperation with the private sector, and the implementation of sustainable programs involving local communities. However, so far there have been limited studies that specifically discuss collaboration models between actors in the local government environment, or cross-sector collaboration with actors such as the business world, universities, the media, and the poor as active subjects. Furthermore, the theoretical approach based on Institutional Analysis and Development (IAD) developed by Elinor Ostrom has not been widely utilized in understanding collaborative relationship patterns and governance in poverty alleviation. Therefore, this study is structured as a literature review that aims to summarize and examine collaboration models that have been applied, as well as identifying empty spaces in scientific discourse. It is hoped that the results of this study can be a conceptual basis that strengthens fair, participatory, and contextual collaboration practices in efforts to reduce extreme poverty in the region.